Language aptitude and working memory in third language learning - Öztekin, Elifcan. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2023., 2023)
This study investigated the relationships of visuospatial and verbal working memory (WM) tasks with language aptitude (LA) and their predictive roles in explaining third language (L3) comprehension. The participants were 110 L1 Turkish-speaking majors in English language teaching, who studied various additional foreign languages for varying numbers of semesters at beginner, intermediate, and upper-intermediate / advanced levels, including a control group with no L3. They took the LLAMA version 3 (Meara & Rogers, 2019), forward digit span, rotation, symmetry, and operation span tasks (Foster et al., 2015). Participants learning one of the four designated European languages (i.e., German, French, Italian, and Spanish) also took reading and listening comprehension sections of general proficiency tests created by the certified cultural institutes. Principal component analysis (PCA) revealed a three-factor solution, interpreted as verbal/phonological memory (digit span, operation span, and partially LLAMA D), visuospatial WM (symmetry and rotation span), and LA (LLAMA B, E, F, partially D). Univariate analyses of variance on the three factors did not reveal any significant relationships with L3 experience. The hierarchical regression on L3 listening comprehension indicated that L3 experience and the LA factor cumulatively explained 45% of the variance, with the LA factor contributing an additional 15% of the variance. The same set of predictors did not explain any significant variance in L3 reading comprehension. The study confirmed the dissociation between certain LA and WM abilities, but some overlap in verbal/phonological/memory abilities. The distinctive LA factor was considerably influential for L3 listening but not reading comprehension.
Keywords: Multilingualism.; Short-term memory.